Computer Vision in Dentistry - Elzbieta Machoy, Monika (Biomedical Engineering, 2019)
The currently available technical and technological solutions of visualization in dentistry are a number of possibilities in creating images useful both for dentists and technicians. To gain a three-dimensional image of a patient's face and profile to visualize changes in appearance after applying a specific therapeutic method in the field of prosthodontics or orthodontics is no longer a problem. The same applies to a very accurate scan of the area to be treated - the exact map of the working field, on the basis of which the implementation of even very difficult dental procedures can be easily planned. Equally available are three-dimensional images of the patient's skull. The book presents the newest means and capabilities of visualization in different fields of dentistry.